(untitled) (Annals of Bangladesh Agriculture, 2022)
The Chattogram Hill Tracts (CHT) are witnessing an escalating pace of land use change as a result of population dynamics, economic development, climatic change, greater accessibility, and agricultural technical advancements. The study was conducted in Rwanggchhari and Ruma upazila of Bandarban district, Bangladesh. This study explored farmers’ perception towards land use change and the factors contributing to their perception. Following a proportionate random sampling technique, a total of 120 households were sampled and survey was administered through a predesigned close ended questionnaire. A substantial number of respondents (54%) were more than 40 years old, of whom 51% were educated with an average family size was five. The respondents had an average annual income of BDT 91830. An average land holding was 3.59 acres were seen in the study area and these lands were occupied with agricultural, forest, vegetable lands and also with flat and hilly lands. Meanwhile, 98% farmers maintained medium to higher perception towards the changes of land distribution. In addition, out of eight attributes, three attributes, namely, educational attainment, agricultural training received and hill land ownership had significant influence on the perception of land use change by the respondents. The findings of the study can be utilized by the policy makers and planners of the country to formulate future land distribution policy of the CHT in future. Ann. Bangladesh Agric. (2022) 26 (1) : 75-89